Análise da maturidade de processos na gestão da TI em empresas do setor de geração e transmissão de energia elétrica - Silva, Fernando Cesar Almeida (2013)
The quality of software and IT services is a requirement that meets the needs of customers and regulatory frameworks such as Sarbanes - Oxley. They are motivators for the implementation of IT governance in organizations. For this reason, the adoption of Business IT Management becomes necessary. There is a lot of Reference Models for the Management of IT available. The strategic planning has an important role as the glue of issues relating to IT processes. This paper presents a survey of maturity of the CobiT processes within companies of the Eletrobras System which presents results and define selection criteria for processes based on criteria of CobiT and the PCAOB. It is presented a literature review of models of IT management CobiT, ITIL, CMMI, PMBOK and MPS.BR. It is also proposed for future work a system for identifying problems and correcting their causes in IT Management processes together using the search CobiT maturity of processes, the Ishikawa diagram and the PDCA cycle